ASPECTS REGARDING THE HOUSE, EDUCATION AND HEALTH INFRASTRUCTURE IN SOUTH-MUNTENIA REGION - Elena LASCĂR (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The infrastructure contains a supporting element, with a special importance to support all economic, social and cultural activities in the rural area. The infrastructure covers both structural area giving unity to the system and space area, thus creating a viable territorial configuration, which is reflected by different levels of accessibility. It is actually the circulatory framework of the economic and social system, individualized in a well determined space, as the regional one. South Muntenia region is characterized by a well defined infrastructure as a result of its advantageous geographical position. Its location in a peripheral area of Romania favored the emergence of major road ways, which allowed the development of its relations not only with neighboring national regions, but also with neighboring country Bulgaria. The present paper analyses the educational and medical infrastructure in the region, showing thus the discrepancies in the education and medical system and equipment across the region. It is pertinent analysis allowing the make improvements in this area.